The stress distribution of a primary molar tooth restored with stainless steel crown using different luting cements - Mehmet Sami Guler; Cigdem Guler; Nihal Belduz Kara; Didem Odabasi; Muhammed Latif Bekci (BMC, 2024)
Abstract Background The aim of this study is to evaluate the stress distributions of a primary molar tooth restored with a stainless steel crown (SSC) using resin and glass ionomer luting cements by Finite Element Analysis (FEA). Methods Original DICOM data of a primary molar was used to create a 3D model. One model was prepared as a tooth model with SSC. A 30 μm cement layer was used in model. Two different luting cements were tested in the study: self-cure adhesive resin cement, and glass ionomer cement. Vertical and oblique loads of 330 N were applied to simulate maximum bite force and lateral forces in the occlusal contact areas of the models. Maximum von Mises stress values in the models were evaluated as MPa. Results The maximum von Mises stress value was observed in the force application and general occlusal contact areas for all models. The maximum von Mises stress values were higher in the tooth model with SSC using self-cure adhesive resin cement (478.09 MPa and 214.62 MPa) than in the tooth model with SSC using glass ionomer cement (220.06 MPa and 198.72 MPa) in both vertical and oblique loading, respectively. Conclusions Depending on the magnitude of the bite force on the SSC, fracture of the luting cement materials could occur if the stress exceeds the endurance limit of the luting cement. Cementation with glass ionomer cement may help to reduce stress levels in SSC restorations of primary molars in children.